2016
DOI: 10.1017/pao.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic analyses of tissue coccidia (sarcocystidae; apicomplexa) based on nuclear 18s RDNA and mitochondrial COI sequences confirms the paraphyly of the genus Hammondia

Abstract: Partial mitochondrial cytochrome c oxidase subunit I (mt COI) sequences were generated from: Toxoplasma gondii (strains 18S rDNA and COI sequences were Bayesian analysed using partitioned nucleotide substitution models [HKY + I + G for 18S; GTR + I + G codon (code = metmt) for COI]. Phylogenetic hypotheses supported a monophyletic Sarcocystidae and its subfamilie with two major clades within the Toxoplasmatinae: (1) a monophyletic clade of Cystoisospora spp. with Nephroisospora eptesici; and (2) a clade of Tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 64 publications
(171 reference statements)
1
10
0
Order By: Relevance
“…5 ); bootstrap support for this scenario was relatively weak (62–74%). Such a tree topology has been observed previously for the tissue coccidia and was attributed to potential lack of key species ( Ogedengbe et al, 2016 ). We were able to remedy this situation by excluding the 3rd codon position from phylogenetic analysis, which resulted in almost the same tree, but rendered the Toxoplasmatinae and Sarcocystinae as separate, monophyletic subclades of the Sarcocystidae.…”
Section: Resultssupporting
confidence: 73%
“…5 ); bootstrap support for this scenario was relatively weak (62–74%). Such a tree topology has been observed previously for the tissue coccidia and was attributed to potential lack of key species ( Ogedengbe et al, 2016 ). We were able to remedy this situation by excluding the 3rd codon position from phylogenetic analysis, which resulted in almost the same tree, but rendered the Toxoplasmatinae and Sarcocystinae as separate, monophyletic subclades of the Sarcocystidae.…”
Section: Resultssupporting
confidence: 73%
“…Numerous phylogenetic studies have focused on the analysis of 18S, 28S, ITS, and cox1 genes, and 18S and cox1 genes have been commonly used for coccidians belonging to the families Sarcocystidae and Eimeriidae ( Carreno et al, 1998 ; Morrison et al, 2004 ; Ogedengbe et al, 2011 , 2016 ). The coccidian 18S sequence is phylogenetically useful for distant taxa, but seems to be much less variable than that in other protozoan parasites and to be insufficient for resolving the relationships among closely related coccidian species ( Morrison et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the cox1 sequence provides sufficient sequence divergence for studying phylogenetic relationships among closely related coccidian species. Ogedengbe et al (2016) made specific cox1 primers for Sarcocystidae groups and suggested that cox1 sequences from sarcocystids (i.e., Toxoplasma , Neospora , and Hammondia ) appeared well suited for species delimitation; however, sequences from Cystoisospora spp. showed remarkably limited sequence variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations